1982
DOI: 10.1007/bf01868488
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode studies of the effect of lanthanum on the electrical potential and resistance of outer and inner cell membranes of isolated frog skin

Abstract: Microelectrodes were used to investigate the effect of 0.5 mM mucosal lanthanum (La3+) on the intracellular potential and the resistance of outer and inner isolated frog skin (Rana esculenta) cell membranes. Under short-circuit conditions, the transapical membrane potential Vsco (mean value = -65.4 +/- 3.2 mV, inside negative) hyperpolarized to -108.7 +/- 2.3 mV in control skins, after addition of the sodium blocker amiloride. Current-voltage curves for the outer and inner membranes were constructed from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…A possible explanation can be found in the work of Adams et al [1], where a single-point mutation in BNaC1 (ASIC2), G430C, created an activatory binding site for Zn 2+ . A similar mechanism could explain the activatory effect of lanthanides applied on the apical side of A6 epithelia (B. Amuzescu, unpublished data) or frog skin [11,12].…”
Section: Discussionmentioning
confidence: 85%
“…A possible explanation can be found in the work of Adams et al [1], where a single-point mutation in BNaC1 (ASIC2), G430C, created an activatory binding site for Zn 2+ . A similar mechanism could explain the activatory effect of lanthanides applied on the apical side of A6 epithelia (B. Amuzescu, unpublished data) or frog skin [11,12].…”
Section: Discussionmentioning
confidence: 85%
“…Employing the sequential technique, Goudeau et al reported a value of V r = 119 mV for skins of Rana esculenta [7]. Using the same technique, Schoen and Erlij found values of 144 and 132 mV in chloride and sulfate Ringer's, respectively, in Rana catesbiana [18].…”
Section: Discussionmentioning
confidence: 92%
“…[Amiloride inhibition has been used in this fashion in studies of frog skin (Fuchs et al, 1977;Goudeau et al, 1982) to extract transcellular Na + currents. Likewise, ouabain binding to the animal Na+,K § ATPase, which affects charge movements in both directions (Skou & Norby, 1979;Karlish & Stein, 1982), meets this criterion.]…”
Section: Voltage Sensitivity and Etransmentioning
confidence: 99%
“…Difference I-V characteristics derived in this fashion have been used to characterize both primary electrogenic ion pumps and secondary transport of organic and inorganic solutes in the fungus Neurospora (Gradmann et al, 1978;Sanders et al, 1983;Blatt et al, 1984;, the giant algae Acetabularia (Gradmann, 1975) and Chara (Walker et al, 1979;Beilby & Walker, 1981 ;Beilby, 1984;Kishimoto et al, 1984;Takeuchi et al, 1985), and a liverwort, Riccia (Felle, 1980(Felle, , 1981aJohannes & Felle, 1985). Current subtractions of steady-state I-V curves have also been used to extract voltage-dependent features for active Na + transport in snail neurones (Kostyuk et al, 1972), a putative K + conductance in L-cells (Roy & Okada, 1978), and ionic components of transcellular pathways in frog skin (Fuchs et al, 1977;Goudeau et al, 1982). Now, there are two main assumptions which underly current subtraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation